2018
DOI: 10.1038/s41525-018-0058-3
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent loss of heterozygosity correlates with clinical outcome in pancreatic neuroendocrine cancer

Abstract: Pancreatic neuroendocrine tumors (pNETs) are uncommon cancers arising from pancreatic islet cells. Here we report the analysis of gene mutation, copy number, and RNA expression of 57 sporadic well-differentiated pNETs. pNET genomes are dominated by aneuploidy, leading to concordant changes in RNA expression at the level of whole chromosomes and chromosome segments. We observed two distinct patterns of somatic pNET aneuploidy that are associated with tumor pathology and patient prognosis. Approximately 26% of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 61 publications
6
48
0
Order By: Relevance
“…However, in this study series, G2 tumours (coinciding with the RPCL cluster) harbouring mutations in DAXX/ATRX and correlating with mutations in mTOR genes were associated with poor prognosis. Another recent targeted/whole-genome sequencing study reported three CN-based clusters (Lawrence et al 2018) similar to those identified in the Scarpa study. Correlation with clinical data demonstrated that tumours in cluster 1 had the poorest prognosis, cluster 2 tumours had more favourable clinical/pathological outcomes, while those in cluster 3 had variable clinical outcomes.…”
Section: Integrated Multi-omic Data Approachessupporting
confidence: 64%
See 1 more Smart Citation
“…However, in this study series, G2 tumours (coinciding with the RPCL cluster) harbouring mutations in DAXX/ATRX and correlating with mutations in mTOR genes were associated with poor prognosis. Another recent targeted/whole-genome sequencing study reported three CN-based clusters (Lawrence et al 2018) similar to those identified in the Scarpa study. Correlation with clinical data demonstrated that tumours in cluster 1 had the poorest prognosis, cluster 2 tumours had more favourable clinical/pathological outcomes, while those in cluster 3 had variable clinical outcomes.…”
Section: Integrated Multi-omic Data Approachessupporting
confidence: 64%
“…However, their penetrance among PanNET cases is currently unknown and warrants further investigation possibly within a clinical genetic referral context. This list has recently been expanded through the identification of novel non-synonymous germline mutations in PIF1 (n = 2), involved in transcriptional regulation and chromatin remodelling, MAPKBP1 (n = 1), a member of the MAPK/ERK signalling pathway (Vandamme et al 2019) known to be co-activated with the PI3K/Akt/mTOR pathway in neuroendocrine tumours through PI3K (Carracedo et al 2008), and identification of a pathogenic germline variant leading to somatic loss of ATM (Lawrence et al 2018).…”
Section: Novel Findingsmentioning
confidence: 99%
“…The cohort includes tumors of grades NET G1 (27) and NET G2 (25) NET G3 (4), and NEC (3), 45 samples were primary PanNENs and 14 were metastases (8 liver, 6 lymph nodes). As healthy control we used matched adjacent healthy (24) or distant healthy tissue (27) or blood (4) from the same patient.…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In addition to driver mutations affecting individual genes, copy number aberrations (CNA) have been used to characterize these tumors 16,[24][25][26] . Recent work has revealed four distinct subtypes based on chromosome arm length CNA patterns: i) recurring copy number losses of specific chromosomes, ii) limited copy number events with mostly loss of chromosome 11, iii) polyploidy tumors and iv) aneuploidy tumors 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation